Effects of two different exercise programs on gait in children with scoliosis diagnosed Juvenile Idiopathic Arthritis - Kısa, Eylül Pınar; Leblebici, Gökçe; Tarakcı, Ela; Kasapçopur, Özgür (Gait & posture, 2023)
Juvenile Idiopathic Arthritis (JIA) is one of the common chronic diseases in childhood. Problems such as weakness or pain may occur in JIA, especially in the joints and the muscles around the trunk (1). These conditions may lead to abnormal displacement of the center of gravity, deterioration of biomechanics, and muscle imbalance in children with JIA (2, 3). All these situations can lead to scoliosis, which we often encounter in children with JIA. Current studies describing various 3-dimension (3D) exercise methods (SEAS, Schroth, Dobomed, BSPTS, Side-shift, Lyon, etc.) effective on scoliosis (4). However, no study was found in the literature that searching the effects of these exercise methods on gait parameters in children with scoliosis diagnosed JIA. What are the effects of Pilates exercise program against the 3D exercises on gait parameters in children with scoliosis diagnosed JIA? 50 children (11,58±3,62 years) with adolescent idiopathic scoliosis (AIS) diagnosed JIA included and randomly divided into 2 groups. Structured 3D scoliosis exercises were applied to the first group (n=25), and Pilates exercises (posture exercises and core stabilization exercises) were applied to the second group (n=25). Trunk rotation angles (ATR) were evaluated using a scoliometer. Cobb angle was measured using the SubrotoAngleAid application on x-ray. Center of force mass (CoM) displacement and maximum pressure were obtained using the FreeMed baropodometry platform (the FreeStep v. 1.0. 3 88 software, Sensor Medica, Guidonia Montecelio, Roma, Italy). To understand the changing between groups, Mann-Whitney U test was conducted. Paired Sample T test was conducted for comparison before and after treatment in groups. While Cobb angle and ATR improved in both groups, Group I showed a more significant improvement compared to Group II. There was no significant difference in CoM displacement between groups and within groups, but the change after treatment in the Pilates group at the dominant side was bigger than 3D structured exercise group (Table). Also maximum loading increased in group II after intervention (Table). [Display omitted] 3D structured and conventional exercise programs has the similar effects on ATR and Cobb angle in children with JIA. However, conventional exercise program increased the maximum loading during gait despite of the current literature (5). CoM displacements changed less in the Pilates group compared to the structured 3-dimensional exercise group, after the treatment at the dominant side. The CoM displacements with less deviation from the weight transfer trajectory in in children with AIS diagnosed with JIA contributes to maintaining dynamic balance during walking (6,7). According to these results, Pilates exercises may be superior to three-dimensional exercises to improve weight transfer and increase dynamic balance in children with AIS diagnosed with JIA.